"WHY I CAN'T SPEAK UP? ": STUDENTS' ANXIETY IN PUBLIC SPEAKING - Ayuning Tiyas; Yayah Nurhidayah; Rama Dwika Herdiawan (Journal of English Language Learning, 2019)
Abstract- Public speaking is a way to talks with individual or group listener with sharing ideas and influencing them either direct or via electronic communication to achieve a specific goal. The aims of this research are to explain what the factors influencing students’ anxiety in public speaking and explain how the students anticipate their anxiety in public speaking. This research used qualitative method. The instruments of this research are observation and interview. The results of this research are the students feel fear of making mistakes, fear of embarrassed, fear of being laughed, always thinking and self-conscious. In addition, assuming all audiences are friends, try to be confident, pray so that they are calm, change the mind set of "I can” continue to try and not become a burden are the way to anticipates their anxiety when public speaking.Keyywords: Anxiety, Speaking, Public Speaking